On the correlations between the largest foreshocks and mainshocks of earthquake sequences in Taiwan - Chen, Kou-Cheng; Kim, Kwang-Hee; Wang, Jeen-Hwa (Frontiers in Earth Science, 2023)
We collect a data set of mainshocks and their respective largest foreshocks of 38 earthquake sequences in Taiwan. The plot of local magnitude, ML, of a mainshock (denoted by MLm) versus ML of its largest foreshock (denoted by MLf) shows an increase in MLm with MLf. This indicates that for Taiwan's earthquakes the bigger the largest foreshock is, the larger the mainshock is. The plot of the epicentral distance, ∆ (in km), from the largest foreshock to the mainshock versus ML of the mainshock exhibits a weak increase in ∆ with MLm as ∆<10 km. The plot of the focal depth of the largest foreshock and that of the mainshock shows a linear increase in the former with the latter for most of event-pairs. Let T be the interval between the occurrence time of the largest foreshock and the mainshock. The plot of T versus MLm exhibits that the mainshock will occur within 5 days, with the highest probability of 1 day, after the occurrence of the largest foreshock. Let H be the hypocentral distance between the largest foreshock and the mainshock. The plot of T versus H reveals a slight increase in T with H when T>1 day.